918
reputation
2
8
21

JMP

Computer Graphics

crystal lattice

Chinese Remainder Theorem

$x=bm^2 + a(m+1)$ solves $x\equiv a \pmod m \land x\equiv b \pmod{m+1}$.
$x=2k^2(a+b) + k(a-b)$ solves $x\equiv a \pmod{2k-1} \land x\equiv b \pmod{2k+1}$.
$x=a(3k+r+3)((3-r)k+1)+b(3k+r)(rk+2r-1)$ solves $x\equiv a \pmod{3k+r} \land x\equiv b \pmod{3k+r+3}$.

Consider 3k+r, 3k+r+3 where r=1 or 2. Then:
(3k+r+3)((3-r)k+1) gives 50: 1mod7, 0mod10, and 33: 1mod8, 0mod11
(3k+r)(rk+2r-1) gives 21: 0mod7, 1mod10, and 56: 0mod8, 1mod11

27
answers
1
question
~73k
people reached

Top tags (57)

Score 8
Posts 1
Posts % 4
Score 8
Posts 1
Score 7
Posts 3
Score 6
Posts 1
Score 5
Posts 1
Score 5
Posts 1

Top posts (28) All Questions Answers | Votes Newest

View all questions and answers

Badges (31)

Gold

2

Rarest

Silver

8

Rarest

Bronze

21

Rarest